Jerusalem : caught in time - Osman, Colin (American University in Cairo Press, 1999)
"The significance of the city of Jerusalem to the world's Muslims, Christians, and Jews cannot be overstated. Jerusalem: Caught in Time captures a bygone era in this holy city, allowing the reader to become acquainted with the city as it was a century ago. Based on a treasure chest of photographs from the archives of the Plestine Exploration fund, this beautifully illustrated volume presents a compilation of images from the middle of hte nineteenth century until the First World War. Collected with the aim of recording the most minute details of the city and the surrounding area, they include the first photographic survey of Jerusalem and present a unique record of the country. Rather than viewing Jerusalem trough a political, religious, or missionary lens, the photographs chronicle everything from archeological digs to the ordinary people of the city going about their daily business.The photographs and accompanying text of Jerusalem: Caught in Time provide a remarkable window into the Jerusalem of the nineteenth and early twentieth centuries and reveal the true face of the city and its people."